1996
DOI: 10.1039/cc9960002037
|View full text |Cite
|
Sign up to set email alerts
|

Metalloporphyrinosilicas: a new class of hybrid organic–inorganic materials acting as selective biomimetic oxidation catalysts

Abstract: New hybrid organic-inorganic materials are prepared by hydrolysis and polycondensation, or cocondensation with tetraethoxysilane, of iron porphyrins bearing a trifluorosilyl function; despite their insolubility, these

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 12 publications
3
58
0
2
Order By: Relevance
“…The catalytic yields are similar to those achieved with the SGA-FePor or SGB-FePor catalysts prepared by us, but it may be considered that the catalyst prepared by Battioni et al 63 has an iron porphyrin content of 15 g g -1 (15%), which is 10 times higher than the content in our SG-FePor catalysts (Table 1, 0.8 to 2.1 g g -1 ).…”
Section: Cyclohexenesupporting
confidence: 47%
See 1 more Smart Citation
“…The catalytic yields are similar to those achieved with the SGA-FePor or SGB-FePor catalysts prepared by us, but it may be considered that the catalyst prepared by Battioni et al 63 has an iron porphyrin content of 15 g g -1 (15%), which is 10 times higher than the content in our SG-FePor catalysts (Table 1, 0.8 to 2.1 g g -1 ).…”
Section: Cyclohexenesupporting
confidence: 47%
“…Nonetheless, our catalysts led to similar (Z)-cyclooctene conversion results. For example, Battioni et al 63 reported that the FePor-supported silica system catalyzed the epoxidation of cyclooctene by PhIO with high epoxide yields (> 90%), by employing materials with high surface area (ca. 700 m 2 g -1…”
Section: Cyclohexenementioning
confidence: 99%
“…Porphyrins and their metal complexes are very fascinating class of dye molecules whose functions vary from oxygen and electron transport (hemoglobin, cytochrome c) to solar energy transfer (chlorophyll) in photosynthesis. The sol -gel immobilization of porphyrins in suitable matrices has been reported in literature due to the importance of these systems from many points of interest, such as: chemical and biochemical sensing [11 -14], optical limiting [15 -17], hole-burning [18,19] and catalysis [20].…”
Section: Introductionmentioning
confidence: 99%
“…These new materials are also sought for improved optical, 14-17 and electrical 18,19 properties, luminescence, 12,20-25 ionic conductivity, [26][27][28] and selectivity, 29-32 as well as chemical [33][34][35] or biochemical 36-38 activity. Chemical activity is of core importance in functional materials.…”
mentioning
confidence: 99%